Ecosystem service delivery by urban agriculture and green infrastructure – a systematic review - Evans, D.L.; Falagán, N.; Hardman, C.A.; Kourmpetli, S.; Liu, L.; Mead, B.R.; Davies, J.A.C. (Ecosystem services, 2022)
•We systematically review ecosystem service delivery by urban agriculture and green infrastructure.•Green infrastructure and urban agriculture deliver a wide range of ecosystem services.•Community Gardens, Green Spaces, and Parks deliver the most diverse ecosystem services.•Natural, Indoor, and Religious Spaces are under-studied in urban ecosystem services research.•We highlight knowledge gaps and future potential of urban ecosystem services research. The ability for urban ecosystems to deliver provisioning, regulating, cultural, and supporting services is vital for the health, sustainability, and resilience of urban environments. The increasing pressures being placed on urban environments by global climate change and the need to create sustainable food systems contributes to rising interest in green infrastructure and urban agriculture solutions. Yet, few studies have systematically assessed the ecosystem service provision of urban agriculture and green infrastructure in parallel. In this systematic review of 157 peer-reviewed journal articles, we synthesize the benefits and disbenefits of implementing various forms of urban agriculture and green infrastructure for the delivery of ecosystem services in urban areas. While both provide a diverse variety of ecosystem services, our review suggests that some services are provided more prevalently when green infrastructure is solely adopted (e.g., Local Climate and Air Quality Regulation), while other services are best delivered when green infrastructure is combined with urban agriculture (e.g., Biological Control and Maintenance of Genetic Diversity). Our data also show that ecosystem service delivery is partly modulated by the spaces in which urban growing takes place. Community Gardens, Green Spaces, Allotments, and Parks are found to be most conducive for diverse service provision, although it is also clear that some growing spaces have not been studied as frequently in urban ecosystem service research. We conclude by highlighting some key research gaps and priorities for urban ecosystem service research, including a stronger focus on under-represented services and growing spaces, the need for more systematic data collection, and the value of incorporating ecosystem service assessments into wider suitability and cost-benefit analyses.